Control de ingresos y gastos de la Piladora San Francisco para el cumplimiento de las obligaciones a corto plazo - Cevallos Paredes, Holger Marcelino (2019)
The purpose of make a financial control is to be able to know the real state in which the company is being fundamental in all financial management. In this case study based on the control of income and expenses of the "San Francisco" Piladora, were used research technigues and then was dore the analysis of the financial statements of the years 2016, 2017 and 2018 through the application of financial indications in which it is observed that the profits generated during the fiscal years presents unfavorable varations being harmed by external factors to its production and admistration, in addition to the fact that the average collection managed by the company evidences conmitments acquired to short term